Chicagoland dream houses : how a mid-century architecture competition reimagined the American home - Moroney, Siobhan, 1960- (University of Illinois Press, 2023)
"Sponsored by the Chicago Tribune, the 1945 Chicagoland Prize Homes competition solicited designs by mostly unknown architects. The goal: to provide beautiful yet practical houses for returning WWII veterans and middle-class residents of the city and suburbs. In-depth and extensively illustrated, Chicagoland Dream Houses revisits this overlooked chapter in Chicago and architectural history. Organizers conceived the competition to help remedy the postwar housing crisis and it received front-page news coverage and an exhibit at the Art Institute of Chicago. It also had the rare distinction of taking designs from paper to reality, an accomplishment that brought out two hundred thousand people to tour finished homes. Yet the contest ultimately failed in its aim to inspire new home construction that would solve Chicago's housing shortage. Siobhan Moroney situates the competition in its time both socially and architecturally, analyzing floor plans and other materials to reveal how the designs reflected the expectations of middle-class families and the social norms that dictated their everyday lives and aspirations"-- Provided by publisher.
Keywords: Chicagoland Prize Homes Competition, 1945.; Architecture, Domestic -- Illinois -- Chicago -- History -- 20th century.; Suburban homes -- Illinois -- Chicago -- History -- 20th century.; Middle class -- Dwellings -- Illinois -- Chicago -- History -- 20th century.; Architecture and society -- Illinois -- Chicago -- History -- 20th century.; Architecture et société -- Illinois -- Chicago -- Histoire -- 20e siècle.; Architecture and society; Architecture, Domestic; Suburban homes; Illinois -- Chicago; ARCHITECTURE / General; 1900-1999; History